Art market research a guide to methods and sources - McNulty, Tom (McFarland & Co., 2006)
"From the gallery to the auction house, this book explores the major venues of art acquisition. It introduces basic terminology for the art collector and covers the basics of artwork analysis and documentation, including a concise overview of database researching methods and online resources"--Provided by publisher.